ANALISIS PENGARUH RASIO KEUANGAN TERHADAP RETURN ON ASSET BANK PERKREDITAN RAKYAT PADA PT. BPR POLIN JAYA - Mulyadi, Dedi; Din, Alexander (Jurnal Manajemen dan Bisnis Kreatif, 2018)
ABSTRACT Influence Analysis of Financial Ratios Return on Assets Rural Bank in PT . BPR Polin Jaya. The purpose of this study was to obtain empirical evidence and find clarity phenomena and conclusions about the effect of variable Financial Ratios Return on Assets Rural Bank in PT . BPR Polin Jaya This thesis is expected to provide input for the bank and customer management for decision making with regard to CAR, NPL, NIM, ROA, LDR and ROA, and economics in general. This research uses descriptive and verification methods, namely; collecting, presenting, analyzing, and testing hypotheses, and make conclusions and suggestions. From the analysis of research data, obtained the following conclusions: 1. The role of capital adequacy of banks in running the business anyway, is something that absolutely must be met. With the fulfillment of CAR by the bank then the bank can absorb losses suffered, so that the activities carried out will be run efficiently, and ultimately the profits from the bank is increasing. 2. The role of the bank's management is very cautious in lending to borrowers so as to minimize loans become problematic 3. The ability of banks to earn interest income from the good and bad effect on the bank's Return on Assets. If the acquisition of the bank NIM ratio increases, the Return on Assets (ROA) of the bank will also increase. 4. The level of efficiency of the bank's operating costs greatly affect the Return on Assets. The more efficient or small bank operating costs, the profit gained greater 5. The level of liquidity of a bank affects the bank's Return on Assets. The more optimal level of liquidity the bank, then the third party funds disbursed in the form of greater credit. With the growing amount of credit granted, the profits to be gained are also getting bigger 6. Effect of CAR, NPL, NIM, ROA, LDR simultaneously significant effect on ROA of 92.7% From these results, it can be concluded that the Return on Assets can be influenced by CAR, NPL, NIM, ROA, LDR, which means Return on Assets can be enhanced through improved CAR, NPL, NIM, ROA, LDR accordance with the regulations of Bank Indonesia and Otoritas Jasa Keuangan. Keywords: CAR, NPL, NIM, BOPO, LDR dan ROA